Influence of soil chemical properties on relative abundance of arbuscular mycorrhiza in forested soils in Malaysia - Ong, Kian Huat; Chubo, John Keen; Sipen, Philip; King, Jie Hung (2012)
Th eeff ect of soil chemical properties on the diversity and colonization of arbuscular mycorrhiza (AM) varies among ecosystems. This study was conducted to assess and compare the abundance of AM in a rehabilitated forest and a logged-over forest soil using the most probable number and spore number methods. Glomus (71.7%-82.1%) and Acaulospora (17.4%-19.5%) were found to be abundant in both sites, while Gigaspora was found only in the loggedover forest. Th e abundance of AM in the rehabilitated forest based on the spore count was signifi cantly higher than in the logged-over forest by a 6-fold diff erence. Furthermore, root colonization in the rehabilitated forest was found to be almost 9-fold higher than in the logged-over forest. Such diff erences are linked to the soil chemical properties. The addition of organic matter during forest rehabilitation activity had created favorable conditions for AM sporulation. Soil P in both forests was positively related to the spore count (r > 0.68, P < 0.001) while the most probable number (MPN)was negatively infl uenced by soil K (r = –0.632, P <0.01). In conclusion, this study showed that soil chemical properties have a direct eff ect on the abundance of AM.